2005
DOI: 10.1136/tc.2003.005470
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness of a community based research project to help women quit smoking

Abstract: Objective: To estimate the cost effectiveness of a four year, multifaceted, community based research project shown previously to help women quit smoking. Design: A quasi-experimental matched control design. Setting: Two counties in Vermont and two in New Hampshire, USA. Subjects: Women aged 18-64 years. Methods: Costs were the grant related expenditures converted to 2002 US$. Survey results at the end of the intervention were used to estimate the numbers of never smokers, former smokers, light smokers, and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Health outcomes are reported where evidence exists or where they can be derived through modelling [22,23]. Life years gained or quality adjusted life years (QALYs) are also sometimes estimated [24][25][26][27][28][29][30][31]. However, even these generic measures of outcome can fail to capture the full range of intervention benefits.…”
Section: Introductionmentioning
confidence: 98%
“…Health outcomes are reported where evidence exists or where they can be derived through modelling [22,23]. Life years gained or quality adjusted life years (QALYs) are also sometimes estimated [24][25][26][27][28][29][30][31]. However, even these generic measures of outcome can fail to capture the full range of intervention benefits.…”
Section: Introductionmentioning
confidence: 98%
“…The cost-effectiveness of English smoking treatment services [£684 per quality-adjusted life-year (QALY) on average] is well below the U.K. benchmark of £20,000 per QALY (53). Less is known about the cost-effectiveness of community interventions, but they may be comparable (115). Even in middle-income countries, cessation pharmacotherapy can be highly cost-effective compared with other medical interventions (50).…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…The quit-and-win contests for smoking cessation did not directly assess benefits, but found that the per-participant cost of the 26 contests, which ranged from US$28 to $154, was directly related to participation rates (Segal et al 1998). Only one of the included studies found that community engagement might not be cost-effective for health promotion: Secker-Walker's evaluation of 'Breathe Easy', a multifaceted smoking cessation intervention for women, reported wide confidence intervals around the estimates of cost-effectiveness, meaning that the intervention was not statistically significantly more effective than not intervening (Secker-Walker et al 2005).…”
Section: Health Promotion Interventions: the Economics Of Engagementmentioning
confidence: 93%
“…Interventions were complex and no study was designed to evaluate the cost-effectiveness of a 'community-engagement' component per se. Interventions were designed to reduce HIV infections (Broadhead et al 1998, Pinkerton et al 1998, prevent non-insulin dependent diabetes mellitus (NIDDM) (Segal et al 1998), and reduce smoking prevalence (Shipley et al 1995, Baxter et al 1997, Ratcliffe et al 1997, Ong and Glantz 2005, Secker-Walker et al 2005. The study by Baxter promoted smoking cessation alongside other healthy-heart behaviours such as healthy eating, exercise and weight loss (Baxter et al 1997).…”
Section: Health Promotion Interventions: the Economics Of Engagementmentioning
confidence: 98%
See 1 more Smart Citation